CYR61/CCN1 expression in resected pancreatic ductal adenocarcinoma: A retrospective pilot study of the interaction between the tumors and their surrounding microenvironment. Issue 5 (May 2020) - Abou-Kheir, Wassim; Mukherji, Deborah; Hadadeh, Ola; Saleh, Eman; Bahmad, Hisham F.; Kanso, Mariam; Khalifeh, Mohamad; Shamseddine, Ali; Tamraz, Sally; Jaafar, Rola; Dagher, Christelle; Khalifeh, Ibrahim; et al.
Abstract: Background: CCN1 is an extracellular matrix-associated protein thought to be implicated in tumor-stromal interaction in several solid tumors. The aim of our pilot study was to evaluate the correlation between CCN1 expression in stromal cells, pancreatic intraepithelial neoplasia (PanIN) and pancreatic ductal adenocarcinoma cells in resected pancreatic ductal adenocarcinoma (PDAC) specimens, and correlate that clinically. Methods: A total of 42 paraffin-embedded PDAC tumor specimens were stained for CCN1 and evaluated via immunohistochemical (IHC) analysis. Statistical analysis was performed to correlate between CCN1 expression profiles in tumor tissues and clinicopathological parameters of patients. Results: Our results showed CCN1 (CYR61) gene was highly expressed in PDAC tissues relative to other organ specific tumor tissues. Also, moderate and overexpression of CCN1 in PanIN was associated with PanIN grade 3 tissues. A statistically significant association was found between PanIN CCN1 scores on one hand and cancer stage, cancer grade, and CCN1 expression among ductal tumor cells and adjacent stromal cells on the other hand. Discussion: The associations demonstrated suggest that CCN1 might be contributing to a substantial role in the interaction between the pancreatic tumors on one hand and their surrounding microenvironment and their precursors on the other hand; hence, it might serve as a potential therapeutic target for PDAC. Abstract : Molecular biology; Cancer research; Hepatobiliary system; Pathology; Cancer surgery; Hepatobiliary surgery; Oncology; Evidence-based medicine; Pancreatic ductal adenocarcinoma; CYR61/CCN1; Microenvironment; PanIN